2017
DOI: 10.1074/jbc.m116.773291
|View full text |Cite
|
Sign up to set email alerts
|

The let-7/Lin28 axis regulates activation of hepatic stellate cells in alcoholic liver injury

Abstract: The let-7/Lin28 axis is associated with the regulation of key cellular regulatory genes known as microRNAs in various human disorders and cancer development. This study evaluated the role of the let-7/Lin28 axis in regulating a mesenchymal phenotype of hepatic stellate cells in alcoholic liver injury. We identified that ethanol feeding significantly down-regulated several members of the let-7 family in mouse liver, including let-7a and let-7b. Similarly, the treatment of human hepatic stellate cells (HSCs) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 32 publications
1
54
0
Order By: Relevance
“…Recently published studies have clarified the role of miRNAs in liver fibrosis [29,30,44]. Not surprisingly, miRNAs have been shown to play both an anti-fibrogenic and a profibrogenic role depending on the genes targeted and the nature of the stimulus [2022,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Recently published studies have clarified the role of miRNAs in liver fibrosis [29,30,44]. Not surprisingly, miRNAs have been shown to play both an anti-fibrogenic and a profibrogenic role depending on the genes targeted and the nature of the stimulus [2022,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Up to 90% of circulating miRNAs are associated with proteins, and different miRNAs were enriched in specific extracellular compartments (e.g., let‐7a was predominant in the vesicle‐rich fractions in healthy individuals). We have demonstrated that let‐7 regulates liver inflammation and fibrosis through lin28 . In PSC models we have alternatively shown that an increase of let‐7, by repression of Lin28, improved fibrosis after alcoholic liver injury and decreased tissue inhibitor of metalloproteinase 3 levels.…”
Section: Discussionmentioning
confidence: 87%
“…(10) We have previously shown that suppression of Lin28 homolog, a downstream target of let-7, increases let-7 and mitigates progression of alcoholic liver disease. (11) Additionally, we have shown that increased let-7 expression as a result of suppression of secretin ameliorated cholestatic liver injury. (10) Let-7, as well as other miRNAs, could be transmitted from stem cells to damaged cells through extracellular vesicles (EVs) to repair or ameliorate damage during liver repair through their downstream targets.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The disruption in Let‐7 and LIN28/28B ratio leads to oncogenesis. These data provide novel insights into molecular mechanisms and argue for new therapeutic approaches for human alcoholic liver fibrosis (McDaniel et al, ).…”
Section: Roles Of Mi‐rnas In Aldmentioning
confidence: 99%